Autophagy responsive intra-intercellular delivery nanoparticles for effective deep solid tumor penetration - Fengling Wang; Dandan Xie; Wenjing Lai; Min Zhou; Jie Wang; Rufu Xu; Jingbing Huang; Rong Zhang; Guobing Li (Journal of Nanobiotechnology, 2022)
Abstract Deep tumor cells (cells in the center of solid tumors) play a crucial role in drug tolerance, metastasis, recurrence and microenvironment immune suppression. However, their deep location endows them with an untouched abdomen and makes them refractory to current treatments. Herein, we exploited the characteristic of higher autophagy in deep tumor cells than in superficial tumor cells and designed autophagy-responsive multifunctional nanoparticles (PGN) to enhance drug accumulation in deep tumor cells. PGNs were prepared by densely coating poly (lactic-co-glycolic acid) (PLGA) with cationic autophagy-responsive cell-penetrating peptide (GR9) and anionic 2,3-dimethylmaleic anhydride (DMA)-modified DSPE-PEG. The suitable nanoparticle size (122.4 nm) and charge-neutral surface (0.21 mV) of the NPs enabled long blood circulation. The hydrolysis of surface-anchored anionic DMA in the acidic microenvironment led to the exposure of the GR9 peptide and enhance tumor penetration. Once the PGN arrived in deep tumor cells with strong autophagy, GR9 was cut off by an autophagy shear enzyme, and the nanoparticles remained in the cells to undergo degradation. Furthermore, we prepared docetaxel (DTX) and chloroquine (CQ) loaded d-PGN. CQ inhibits autophagosome fusion with lysosomes, resulting in autophagosome accumulation, which further enhances the sensitivity of d-PGN to autophagy and their deep tumor retention. In vivo experiments showed that drug-loaded d-PGN achieved excellent antitumor efficacy with a peak inhibition rate of 82.1%. In conclusion, autophagy-responsive multifunctional nanoparticles provide a novel potential strategy for solid tumor treatment.